Narrow linewidth 80 W tunable thulium-doped fiber laser. (February 2022) - Cook, Justin; Roumayah, Patrick; Shin, Dong Jin; Thompson, Jasmine; Sincore, Alex; Vail, Nicholas; Bodnar, Nathan; Richardson, Martin
Highlights: A narrow linewidth, tunable 80 W thulium fiber laser is presented. Low doping concentration thulium fiber was used to avoid thermal degradation. System performance was optimized to investigate thermal blooming. Effects of thermal blooming on laser propagation have been investigated. Abstract: We describe the design and characterization of a tunable narrow linewidth thulium-doped fiber laser source which combines a core-pumped preamplifier and high power cladding-pumped amplifier, providing >80 W average power. The single-frequency wavelength output from 1.92 um to 2.01 µm is digitally tunable to target specific atmospheric absorption and transmission windows for applications targeting atmospheric transmission at 2 µm. Results from preliminary thermal blooming studies are presented.